A multifunctional acetyl-CoA carboxylase gene confers freesing tolerance in arabidopsis thaliana - Amid, Azura; Warren, Garreth J. (Asian Network for Scientific Information, 2009)
The sfr3-1 mutation causes freezing-sensitivity in Arabidopsis thaliana. Through mapping, sequencing and transgenic complementation, sfr3-1 was revealed as a missense mutation in ACC1, which is an essential gene encoding multifunctional acetyl-CoA carboxylase. Suppression of ACC1 expression by RNA interference produced a freezing-sensitive phenotype with some similarity to that of sfr3-1. The dCAPS primers and PCR confirmed that sfr3 gene encodes multifunctional acetyl-CoA carboxylase. Microarray and real-time PCR experiments demonstrated that the expression of ACC1 increase only 1.48 fold in wild-type and 1.35 fold in mutant in response to cold treatment. Studies also suggested that the sfr3-1 mutation is more likely to be a temperature-sensitive mutation as the sfr3 mutant cuticle becomes leaky only at low temperature and this was confirmed by cuticular defects analysis.